Prevention of violence against women and girls : mainstreaming in development programmes - Bradley, Tamsin; Gruber, Janet (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Prevention of Violence Against Women and Girls argues that women and girls are vulnerable across all areas of society, and that therefore a commitment to end violence against women and girls needs to be embedded into all development programmes, regardless of sectorial focus. This book presents an innovative framework for sensitisation and action across development programmes, based on emerging best practices and lessons learnt, and illustrated through a number of country contexts and a range of programmes. Overall, it argues that SDG 5 can only be achieved with a systematic model for mainstreaming an end to violence against women and girls, no matter what the priorities of the particular development programme might be. Demonstrating how the approach can be applied across contexts, the authors explore cases from the energy sector, health and humanitarian intervention, and from countries as varied as South Sudan, Myanmar, Rwanda, Nepal, and Kenya. Drawing on nearly three decades of experience working on gender, health and violence against women programmes as both practitioners, and academics, the authors present key lessons which can be used by both students, researchers and practitioners alike"--
Introduction 1 Theorising violence against women and girls 2 VAWG mainstreaming -- a framework for action 3 Women, internal displacement, and violence in Nepal and Myanmar 4 Focus on VAWG in humanitarian emergencies: the scale of the problem and responses 5 VAWG prevention and response in humanitarian emergencies: an overview of current approaches and gaps in knowledge 6 VAWG and conflict: focus on women, peace, and security 7 The rule of law, women's rights, and VAWG prevention and response 8 How to mainstream VAWG across sectors: two examples from modern slavery and sustainable energy programming 9 Funding for VAWG prevention and response: gaps and opportunities Conclusion: the Covid-19 pandemic and implications for VAWG prevention and response and gender equality
Keywords: Women -- Violence against; Girls -- Violence against; Gender mainstreaming; SOCIAL SCIENCE / Gender Studies; SOCIAL SCIENCE / Third World Development